PENERAPAN BUDAYA RELIGIUS MELALUI METODE NASEHAT DAN METODE PEMBIASAAN BAGI SISWA SD ISLAM EXCELLENT PLUS BUKITTINGGI - Alfi Sukrina; Charles; Fadhila Yusri; Junaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the general description of religious culture for students of Excellent Plus Bukittinggi Islamic Elementary School and to explain the efforts of PAI teachers in implementing religious culture through the advice method and habituation method. This research uses qualitative methods with a phenomenological approach and uses data collection techniques of observation, interviews, and documentation and analysis techniques with data reduction, data presentation and drawing conclusions. The results showed that: 1) The general description of religious culture for Excellent Islamic Elementary School students is the 6S culture (smile, greeting, greeting, polite, courteous and patient), the morning muraja'ah program together every Tuesday and Wednesday in the school yard, praying sunnah dhuha in congregation every Friday in the school musola, performing zuhur and asar prayers every Monday - Friday in the school musola, cultivating dhikr and istigosah (praying together) after every prayer in congregation and collecting donations every Friday morning in the school yard. 2) Efforts to implement a religious culture through the method of advice by socializing the school's religious culture by providing reinforcement material containing motivation at the beginning of the new school year, and establishing cooperation with all teachers in advising students in implementing a religious culture and advising students with language techniques and soft and firm speech. 3) Efforts to familiarize students in applying the school's religious culture by giving positive reinforcement, accustoming students from an early age to implement the school's religious culture and routinizing the implementation of the school's religious culture programmatically, then conducting controlled supervision